2017
DOI: 10.18178/ijiet.2017.7.12.988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Computer-Assisted Intervention on Early Phonological Processing Skills for Kindergarten Children in Hong Kong

Abstract: Abstract-The present study investigates the effect of computer-assisted intervention targeting phonological processing skills in Hong Kong kindergarteners who learn English as a second language (ESL). Thirty children received 18 sessions of 45 minutes phonological processing skills intervention over nine weeks. Children in the experimental group (n = 15) received computer-assisted intervention, while the control group (n = 15) received intervention by traditional (pencil-and-paper) teaching approach. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…RTE can only be made a success if India steps forward towards inclusive education and to attain that goal computer-assisted learning intervention can prove to be an important tool in the armory of educators. Lastly, if the effectiveness is proved for such computer-assisted cognitive interventions in enhancing the learning skills of children, then the learning software can also be used as a study aid not only for children with a learning disability but for the improved performance of normal school-going children too (Law, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RTE can only be made a success if India steps forward towards inclusive education and to attain that goal computer-assisted learning intervention can prove to be an important tool in the armory of educators. Lastly, if the effectiveness is proved for such computer-assisted cognitive interventions in enhancing the learning skills of children, then the learning software can also be used as a study aid not only for children with a learning disability but for the improved performance of normal school-going children too (Law, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another important research was done by (Law, 2017) to evaluate the effectiveness of computer-assisted intervention targeting phonological processing skills for normal kindergarten children in Hong Kong who learn English as a second language. Children in the experimental group and control group were taught with computer-assisted and penciland-paper teaching approaches, respectively.…”
Section: ) Working Memory and Executive Functionmentioning
confidence: 99%
“…According to Jamaluddin et al [20], Jolly Phonics can effectively enhance the phoneme-segmentation ability of learners along with their phonographic and other PA skills, helping learners from rural areas develop their reading skills. Law and Hew [28] compared the results between computer-based Jolly Phonics and conventionally delivered contents of Jolly Phonics. They found that computer-based treatments, such as Computer Assisted Instructions, have statistically positive and significant effects on the alliteration, phoneme segmentation, and rhyming skills of young ESL learners, whereas blending skills have no significant effects.…”
Section: Past Studiesmentioning
confidence: 99%